Design and Analysis of Tripple Band Koch Fractal Yagi Uda Antenna - Satyandra Singh Lodhi; P.K. Singhal; V.V. Thakare (International Journal of Electrical and Computer Engineering (IJECE), 2013)
The proposed antenna is Koch fractal printed Yagi-Uda antenna fed by SMA connector. The radiation characteristics of the antenna are simulated by CST Microwave Studio and analysed with the help of simulated results. The antenna's currents distribution becomes more uniform after being fractal, which is conducive to increase the antenna’s radiation directivity. The proposed Koch fractal Yagi-Uda antenna resonance at frequency of 7.81 GHz, 8.54 GHz and 9.42 GHz with gain of 9.67 dB, 10.4 dB and 10.61dB respectively. Parameter of antenna such as return loss, input impedance, smith chart, radiation pattern is analyzed for performance evaluation of Koch fractal Yagi-Uda antenna.DOI:http://dx.doi.org/10.11591/ijece.v3i4.2572